ANALISIS DETERMINAN RENDAHNYA PEMAKAIAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) - Handayani, Meti; Ellina; Yulizar; Eka Afrika (LPPM STIKes Mitra Adiguna, 2023)
Long-Term Contraceptive Method (MKJP) is a type of contraception that is very effective to avoid birth, regulate birth intervals, and does not affect sexual intercourse that can last for 3 years to a lifetime (Ahyar and Muzir, 2019). The coverage of active family planning participants according to the BKKBN between 2017 was 63.22%, those who chose to use MKJP were 17.45%. In 2018 it was 63.27% while the RPJMN target to be achieved in 2018 was 66%, while family planning acceptors who chose to use MKJP in 2018 were 17.81%. In 2019 it was 62.5% while the RPJMN target to be achieved in 2019 was 66%, while the research design that will be used in this study is descriptive analytic with a cross sectional approach. The sample in this study amounted to 95 respondents. The results of the Univariate Analysis showed that the majority of the respondents who used MKJP were 37 respondents (38.9%) and 58 respondents (61.1%). From the results of the bivariate analysis, it was obtained that the age variable had a value of value 0.045, the parity variable value value 0.036, the educational variable obtained a p value of 0.029, and the history of disease variable obtained a p value of 0.024 where this value <0.05 indicates that there is a significant relationship between age, parity, education and disease history with MKJP